Functional significance of a family of protein kinases encoded at the shaggy locus in Drosophila. - Ruel, L (1993)
The characterization of the structurally complex gene shaggy is presented. This gene encodes multiple proteins with putative serine/threonine kinase activity thought to be involved in signal transduction mechanisms that take place during several patterning events throughout Drosophila development. The gene comprises two transcription units that give rise to 10 transcripts and five different proteins with a common kinase catalytic domain and overlapping patterns of expression during development. Mutational analysis of shaggy defines a single complementation group, lethality of which is associated with the loss of two major shaggy proteins. These studies allow the first definition of a true null allele. Two proteins may fulfill maternal requirements. Phenotypes of flies expressing individual shaggy proteins revealed that although there is some redundancy between the different forms they do not all carry out identical functions in vivo. However, under experimental conditions, a single form of the protein was able to carry out all known requirements. This protein probably also functions as part of a signal transduction cascade in the imaginal neuroepithelium, where cells have to choose between epidermal and neural fates.